1992
DOI: 10.1287/isre.3.4.307
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Investment in Information Technology and Firm Performance: A Study of the Valve Manufacturing Sector

Abstract: Large amounts of resources have been and continue to be invested in information technology (IT). Much of this investment is made on the basis of-faith that returns will occur. This study presents the results of an empirical test of the performance effects of IT investment in the manufacturing sector. Six years of historical data on IT investment and performance was collected for 33 valve manufacturing firms from the CEO, the controller and the production manager in each firm. Investment was perceptually catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
378
0
41

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 676 publications
(431 citation statements)
references
References 38 publications
(28 reference statements)
12
378
0
41
Order By: Relevance
“…In reviewing past research, Weill (1992) commented that not all IT investment is alike and that the context of the "rm is important for converting IT investments into productive outputs. Similarly, Li and Ye (1997) found that the impact of IT investments appear to be dependent on the "rm's contextual factors.…”
Section: Role Of Information Technology (It )mentioning
confidence: 99%
See 2 more Smart Citations
“…In reviewing past research, Weill (1992) commented that not all IT investment is alike and that the context of the "rm is important for converting IT investments into productive outputs. Similarly, Li and Ye (1997) found that the impact of IT investments appear to be dependent on the "rm's contextual factors.…”
Section: Role Of Information Technology (It )mentioning
confidence: 99%
“…A broad de"nition of IT, in accordance with that of Weill (1992), was adopted which includes all hardware, software, communications, telephone and facsimile as well as personnel and resources dedicated to IT, whether centralized or decentralized. In this study, the term &IS' is used interchangeably with &IT'.…”
Section: Instrumentmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, IT only provides comparative and temporary advantage which will diminish when peer firms also implement IT. Earlier research by Weill (1992) argues that, even though IT can improve firm performance through cost reduction and revenue expansion, the competitive advantage may disappear once IT becomes common. show that IT investments make a greater contribution to overall firm risk than do non-IT investments.…”
mentioning
confidence: 99%
“…Organizations that can overcome the cultural and functional barriers involved should reap the benefits through improved returns on their human and IS capital. (Barua et al 1995, Weill, 1992, Soh and Markus 1995.…”
mentioning
confidence: 99%